Targeting AGEs Signaling Ameliorates Central Nervous System Diabetic Complications in Rats - Mohamed Naguib Zakaria; Hany M. El-Bassossy; Waleed Barakat (Hindawi Limited, 2015)
Diabetes is a chronic endocrine disorder associated with several complications as hypertension, advanced brain aging, and cognitive decline. Accumulation of advanced glycation end products (AGEs) is an important mechanism that mediates diabetic complications. Upon binding to their receptor (RAGE), AGEs mediate oxidative stress and/or cause cross-linking with proteins in blood vessels and brain tissues. The current investigation was designed to investigate the effect of agents that decrease AGEs signaling, perindopril which increases soluble RAGE (sRAGE) and alagebrium which cleaves AGEs cross-links, compared to the standard antidiabetic drug, gliclazide, on the vascular and central nervous system (CNS) complications in STZ-induced (50 mg/kg, IP) diabetes in rats. Perindopril ameliorated the elevation in blood pressure seen in diabetic animals. In addition, both perindopril and alagebrium significantly inhibited memory decline (performance in the Y-maze), neuronal degeneration (Fluoro-Jade staining), AGEs accumulation in serum and brain, and brain oxidative stress (level of reduced glutathione and activities of catalase and malondialdehyde). These results suggest that blockade of AGEs signaling after diabetes induction in rats is effective in reducing diabetic CNS complications.